2014
DOI: 10.1016/j.bbamem.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic evaluation of the transfection barriers involved in lipid-mediated gene delivery: Interplay between nanostructure and composition

Abstract: Here we present a quantitative mechanism-based investigation aimed at comparing the cell uptake, intracellular trafficking, endosomal escape and final fate of lipoplexes and lipid–protamine/deoxyribonucleic acid (DNA) (LPD) nanoparticles (NPs) in living Chinese hamster ovary (CHO) cells. As a model, two lipid formulations were used for comparison. The first formulation is made of the cationic lipid 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP) and the zwitterionic lipid dioleoylphosphocholine (DOPC), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 56 publications
(50 reference statements)
1
50
1
1
Order By: Relevance
“…3E and 4E). The mechanism of action of LPD may that a core complex is formed with protamine and DNA, and this complex in conjunction with CLs then forms a LPD nanoparticle with a shell-core structure (9). Moreover, in our study, the size of the nanoparticles decreased following the addition of protamine to form the LPD complexes (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…3E and 4E). The mechanism of action of LPD may that a core complex is formed with protamine and DNA, and this complex in conjunction with CLs then forms a LPD nanoparticle with a shell-core structure (9). Moreover, in our study, the size of the nanoparticles decreased following the addition of protamine to form the LPD complexes (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, previous studies have demonstrated that CL-mediated gene transfer may be enhanced by the addition of natural polycations which act as DNA-condensing agents and form liposome-polycation-DNA complexes. Natural polycations, such as protamine sulfate (8,9), chitosan (10) and poly-L-lysine (11), have been shown to condense DNA and form nanoparticles which are mechanically stable, of uniform particle size and of controllable morphology. Protamine, which is non-toxic and is composed of natural cationic peptides, may provide unique membrane-translocating and nuclear-localizing activities owing to its abundant amino acid sequence (12).…”
Section: Introductionmentioning
confidence: 99%
“…The produced NLS-GFP is used as bright and photo-stable reporter of successful transfection. The "gold-standard" Lipofectamine M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT formulation (hereafter: LFN) is selected as a benchmark for lipid-based DNA transfection 9-11 and compared to the recently introduced alternative formulation made of the neutral lipid 1,2-Dioleoylsn-glycero-3-phosphoethanolamine (DOPE) and the cationic cholesterol derivative 3β-[N-(N′, N′-Dimethylaminoethane)-Carbamoyl]Cholesterol (DC-Chol) (hereafter: DC-Chol/DOPE) 12,13 . This latter has been classified as one of the most efficient vectors for transfection of DNA into cells 14,15 (a schematic representation of a typical experiment is reported in Fig.…”
Section: Textmentioning
confidence: 99%
“…Faz-se necessário padronizar as concentrações dos inibidores utilizando marcadores específicos de cada via que depende do inibidor, do tipo celular e do tempo de exposição. Os marcadores mais utilizados são a transferrina para endocitose mediada por clatrina, 60 toxina da cólera para a endocitose mediada por caveolina 61 e dextrana para macropinocitose. 62 Os marcadores geralmente são disponíveis comercialmente já associados a um fluoróforo.…”
Section: Figura 2 Local De Atuação De Inibidores De Endocitose Nas Vunclassified